FINANCIAL RESILIENCE AND SUSTAINABILITY IN ACEH AQUACULTURE COOPERATIVES LHOKSEUMAWE: ANALYSIS OF THE ROLE OF LIQUIDITY AND SOLVENCY RATIOS - Nurliya; Juliana Putri; Khalish Khairina; Rita Mulyani (Universitas Sultanah Nahrasiyah, 2026)
The financial performance of cooperatives plays an important role in ensuring businesssustainability and member welfare. However, the Aceh Aquaculture Cooperative (AAC)Lhokseumawe during the 2016–2023 period experienced fluctuations in its Remaining OperatingResults (SHU), including a loss in 2017. This condition indicates problems in liquidity and capitalstructure that need to be further analyzed. This study aims to examine the effect of liquidity ratios,proxied by the Current Ratio (CR) and Quick Ratio (QR), as well as solvency ratios, proxied by theDebt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), on the cooperative’s financialperformance. This research employs a quantitative with multiple linear regression analysis. Thedata used are secondary data obtained from the financial statements of AAC Lhokseumawe from2016 to 2023. The results show that partially CR, QR, and DER have a significant effect on SHU,while DAR does not have a significant effect. Simultaneously, all independent variables have asignificant effect on SHU. Thus, proper management of liquidity and capital structure can improvethe financial performance of cooperatives